PTH-066 Specialist nurse-led percutaneous endoscopic gastrostomy insertion and patient assessment in modern-day practice. (23rd September 2015) - Aljabiri, M; Ramdass, D; Joshi, N; Defoe, H; Ramdass, A; van Someren, N; Besherdas, K
Abstract : Introduction: PEG feeding improves prognosis and general state of health when patients cannot maintain adequate nutrition. Some hospitals now have nutrition teams who review percutaneous endoscopic gastrostomy (PEG) requests. The PEG Clinical Nurse Specialist (CNS) can provide information/advice/counselling for patients and relatives on PEG feeding, aftercare and follow-up as well as being an integral part of the Upper GI multidisciplinary team. Methods: Aims: To assess the role of the Specialist nurse lead PEG service in an associate teaching district general hospital (DGH). We retrospectively assessed 178 PEG referrals to the service over the period 2006–2008 in our DGH. All PEG referrals are assessed by a CNS who recommends appropriateness of PEG insertion or deflects inappropriate referrals. Data were obtained from the CNS records along with endoscopy software and from patient's clinical data. Results: 178 PEGs inserted in the period 2006–2008. Of these referrals, 44 (25%) were declined due to ill health and deemed as inappropriate (eg, advanced severe dementia). Of these 44 patients following assessment, 6 (13%) started eating and drinking within 48 h, 3 (6.8%) died within 24 h, 4 (9%) died within 72 h. 144 PEGs were inserted one failed due to difficulty in positioning. 38 (26.5%) were inserted by the CNS, and 105 (73.5%) were performed by 11 doctors in the same period. 11 (7.6%) of these were performed as day-case procedures. The nurse specialist requested a second opinion and consultant review for only six patients (3.3%). The CNS assessed and followed up all the 144 patients prior to PEG insertion and provided aftercare. PEG referrals required 60 min on average per patient assessment by the CNS, furthermore the actual PEG insertion average time was 30 min/patient. There were 2 (1%) complications due to minor bleeding from the skin incision. There were 14.6% (21 patients) deaths recorded at 30 days post insertion. Conclusion: In our experience, specialist nurse led PEG service prevented inappropriate PEG insertion in 25% of all referrals and reduced significant clinical commitment for doctors with only requiring advice from consultant in 3%, saving 250 h of clinical assessment and review time. This service also helped reduce waiting times for patient assessment and improved the quality of the service offered by increasing continuity of care and closer liaison with dietician, ward nurses along with patients and their relatives. Our complication/mortality rates compared favourably at 1% and 15%, respectively, to the BSG announcement in 2006 suggesting that minor complications are around 15% and mortality up to 28%. For a modern day PEG service from our data, we recommend a Nurse Lead PEG assessment/insertion and follow-up service in all hospitals not offering this.